THE EXISTENCE OF COLLATERAL IN CREDIT THROUGH PEER-TO-PEER LENDING SERVICES - Ninis Nugraheni; Qonitah Annur Aziza (Yustisia Jurnal Hukum, 2020)
Recently, the total number of registered P2P Lending Fintech promoters has reached 144 companies after 17 fintech joined in one month and had a business license in October 2019. The status of business lisence conferred to platforms registered in OJK has met a number of requirements such as information security in the form of ISO 271001, digital signature and the principle of risk management. As an “umbrella organizationn” for all fintech companies in Indonesia, Indonesia Fintech Association (i.e., AFTECH) has 280 members, which 250 of them operate their business in digital financing system, online credit, innovation on digital finance, insuretech, equity crowdfunding, and etc. The rapid growth of the fintech industry may definitely make a huge contribution to the Indonesian people, especially for retail and unbanked segments. However, this rapid growth potentially evokes legal problems on its implementation as the implementation of credit on peer-to-peer lending does not bring the engaged parties into person but solely through online-access in addition to its less prudence of making transactions, a default of loans which injures the creditors may likely to happen. The importance of legal protection for creditors by selecting an appropriate mitigation of risks (e.g., fiduciary warrant) as a legal assurance for engaged parties, especially the preferent creditors in terms of  possessing the fiduciary certificate when it comes to default. The result of this study with the fiduciary agreement, it will be prioritized in credit disbursement when the debtor turns into bangkruptcy and thus they are not allowed to use their loans for another purpose